SIMULASI SISTEM ANTRIAN LOKET PARKIR KENDARAAN DI MALL STS (SADANG TERMINAL SQUARE) - Dimas Wismono; Diki Muchtar; Ihsan, Muhammad Ihsan (Sekolah Tinggi Teknologi Wastukancana, 2024)
Vehicle queues formed in front of the gate of the ticket collection counter at STS Mall can cause problems and queue lengths that can interfere with other traffic movement systems. Therefore, it is very important to review the queuing system at the gate of the parking ticket collection counter at STS Mall. This study aims to examine the queuing system and determine alternatives to improve four-wheeled vehicle queuing services at the ticket collection counter to enter the parking lot at STS Mall. The main data needed in this study are vehicle arrival rates and counter service times. The data were obtained respectively using traffic enumeration methods and sampling observations, which were carried out at the entrance counter of four-wheeled vehicles and carried out on Saturdays and Sundays. The analysis method uses Queue Theory. The results of the analysis show that the number of counters 1 piece is still able to serve the current level of vehicle arrivals which gives a value of n ranging from 0.34 - 0.37 vehicles (( 1 vehicle) , q ranging from 0.08 - 0.06 vehicles (( 1 vehicle), d ranging from 8.2 - 8.6 seconds, and w ranging from 2.1 - 2.5 seconds. At an arrival rate above 600 vehicles / hour are no longer able to be served with the number of counters (N) as much as 1 piece without improving the queuing system